THE INVESTIGATION OF SEMI-REGULAR VARIABLE UV BOO - Pikhun, A. I.; Kudashkina, L. S.; Brukhanov, I. S. (Одеські астрономічні публікації, 2017)
Periodogram analysis of the photographic observations of UV Boo based on Hipparcos data has showed two photometric periods: 596 d ± 47 d and 11.d74 ± 0.d01 and the same high peak on the value 10d.60 ± 0.d02. On Odessa plates data have showed three periods: 351.d10 ± 1.d50; 196.d14 ± 0.d41; 10.d442 ± 0.d002.